Finite-element modelling of magnetic fields for superconducting magnets with magnetic vector and total scalar potentials using COMSOL Multiphysics®. (6th June 2022) - Chervyakov, Alexander
The finite-element modelling of superconducting magnets is a resource-hungry and challenging work. For these devices, the high-quality requirements for focusing fields are usually superimposed by complexity of the model geometries and nonlinearity of the magnetic materials. The precise field simulations could result therefore in substantial number of the degrees of freedom and, as a consequence, in significant usage of the computational resources. To achieve the acceptable accuracy with lower number of finite elements, the magnetic field distributions are calculated in terms of the magnetic vector potential (A-formulation) as well as the total scalar potential (V-formulation) with COMSOL Multiphysics® and is compared. For these calculations, we utilise the model of a superconducting dipole magnet recently designed for operation of the compact isochronous cyclotron SC200. The performance of both methods is analysed in terms of accuracy and quality of the obtained fields as well as in terms of the computational cost.